Intraspecific difference of Latilactobacillus sakei in inflammatory bowel diseases: Insights into potential mechanisms through comparative genomics and metabolomics analyses - Yaru Liu; Hui Duan; Ying Chen; Chengcheng Zhang; Jianxin Zhao; Arjan Narbad; Fengwei Tian; Qixiao Zhai; Leilei Yu; Wei Chen (iMeta, 2023)
Abstract Inflammatory bowel diseases (IBDs) are chronic inflammatory diseases of the gastrointestinal tract that have become a global health burden. Studies have revealed that Latilactobacillus sakei can effectively alleviate various immune diseases, including colitis, rheumatoid arthritis, and metabolic disorders. Here, we obtained 72 strains of L. sakei from 120 fermentation and fecal samples across China. In total, 16 strains from different sources were initially screened in an in vitro Caco‐2 model induced by dextran sulfate sodium. Subsequently, six strains (four exhibiting effectiveness and two exhibiting ineffectiveness) were selected for further validation in an in vivo colitis mouse model. The results demonstrated that L. sakei strains exhibited varying degrees of amelioration of the colitis disease process. Notably, L. sakei CCFM1267, the most effective strain, significantly restored colon length and tight‐junction protein expression, and reduced the levels of cytokines and associated inflammatory enzymes. Moreover, L. sakei CCFM1267 upregulated the abundance of Enterorhabdus, Alloprevotella, and Roseburia, leading to increased levels of acetic acid and propionic acid. Conversely, the other four strains (L. sakei QJSSZ1L4, QJSSZ4L10, QGZZYRHMT1L6, and QGZZYRHMT2L6) only exhibited a partial remission effect, while L. sakei QJSNT1L10 displayed minimal impact. Therefore, L. sakei CCFM1267 and QJSNT1L10 were selected for further exploration of the mechanisms underlying their differential mitigating effects. Comparative genomics analysis revealed significant variations between the two strains, particularly in genes associated with carbohydrate‐active enzymes, such as the glycoside hydrolase family, which potentially contribute to the diverse profiles of short‐chain fatty acids in vivo. Additionally, metabolome analysis demonstrated that acetylcholine and indole‐3‐acetic acid were the main differentiating metabolites of the two strains. Therefore, the strains of L. sakei exhibited varying degrees of effectiveness in alleviating IBD‐related symptoms, and the possible reasons for these variations were attributed to discrepancies in the carbohydrate‐active enzymes and metabolites among the strains.